2005
DOI: 10.1210/en.2005-0115
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Residue 155 in the Second Intracellular Loop Plays a Critical Role in Rat Melanin-Concentrating Hormone Receptor 1 Activation

Abstract: Melanin-concentrating hormone (MCH) receptor 1 (MCH1R) is a class A G protein-coupled receptor. The MCH system has been linked to a variety of physiological functions, including the regulation of feeding and energy metabolism. We recently reported the importance of a dibasic motif in the membrane-proximal C-terminal region for MCH1R function. Here we reveal that an Arg residue in intracellular loop 2 of MCH1R plays a critical role in receptor function. We analyzed the roles of two distinct motifs, BBXXB and BX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Furthermore, Arg14 of MCH peptide is an important residue to interact with Asp123 site of MCH1R. Arg155 in intracellular loop 2 of MCH1R has been shown to play a critical role in receptor function since Arg155 mutation led to a drastic loss of MCH1R signal transduction without changing the high affinity constant (Kd) value [34]. Also, a point mutation in Thr255 which is located at the junction of intracellular loop 3 and transmembrane domain 6 resulted in the receptor being retained in the endoplasmic reticulum; it dramatically reduced the MCH1R cell surface expression level.…”
Section: Pharmacological Characteristics Of the Mch Receptormentioning
confidence: 99%
“…Furthermore, Arg14 of MCH peptide is an important residue to interact with Asp123 site of MCH1R. Arg155 in intracellular loop 2 of MCH1R has been shown to play a critical role in receptor function since Arg155 mutation led to a drastic loss of MCH1R signal transduction without changing the high affinity constant (Kd) value [34]. Also, a point mutation in Thr255 which is located at the junction of intracellular loop 3 and transmembrane domain 6 resulted in the receptor being retained in the endoplasmic reticulum; it dramatically reduced the MCH1R cell surface expression level.…”
Section: Pharmacological Characteristics Of the Mch Receptormentioning
confidence: 99%
“…Importantly, we identified the C-terminal five amino acids of G␣ q were involved in the interaction with IL2 of receptors. Previous reports showed that multiple substitution of the basic amino acids are required to abolish the receptor function (34,36); however, replacement of Arg-164 alone in PKR2 with amino acids other than positive-charged ones was able to disrupt the receptor function. Nevertheless, studies on the closely related PKR1 indicated that the equivalent Arg-173 does function cooperatively with surrounding basic amino acids.…”
Section: Discussionmentioning
confidence: 97%
“…Mutation in this region can selectively abolish the G␣ q -coupling of PTH/PTH-related protein receptor but retain the G␣ s -coupling capacity (35). However, Saito et al demonstrated a basic amino acid (Arg-155) in the IL2 of MCHR1 plays a critical role in the G-protein coupling and activation but not selectivity, as both G␣ q and G␣ i -coupled pathway are disrupted by R155Q mutation (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, four epitope domains (amino acids 51-80, 85-98, 154-158, 254-260) have been identified as the antibody binding sites (10). Also, the equivalent peptide sequence to epitopes 51-80 and 85-98, 154-158 and 254-260 in rat McHR1 are predicted to lie in the extracellular N-terminal domain, the first extracellular loop, and the second extracellular loop of the receptor, respectively (19).…”
Section: Discussionmentioning
confidence: 99%